2009
DOI: 10.1124/jpet.109.157446
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Antinociceptive and Antirewarding Profiles of Novel Bifunctional Nociceptin Receptor/μ-Opioid Receptor Ligands: Implications for Therapeutic Applications

Abstract: The nociceptin receptor (NOPr), a member of the opioid receptor family, is a target for the treatment of pain and drug abuse. Nociceptin/orphanin FQ (N/OFQ), the endogenous peptide for NOPr, not only modulates opioid antinociception, but also blocks the rewarding effects of several abused drugs, such as morphine, cocaine, and amphetamine. We hypothesized that NOPr agonists, with bifunctional activity at the -opioid receptor (MOPr), may function as nonaddicting analgesics or as drug abuse medications. Bifunctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
91
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 75 publications
(97 citation statements)
references
References 36 publications
6
91
0
Order By: Relevance
“…In a previous study, we have shown that SR14150 produces antinociception in the tail-flick assay in animals that are not in chronic pain (Toll et al, 2009). Likewise, here we report that SR14150 produces an increase in tail-flick latency in SNL animals.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a previous study, we have shown that SR14150 produces antinociception in the tail-flick assay in animals that are not in chronic pain (Toll et al, 2009). Likewise, here we report that SR14150 produces an increase in tail-flick latency in SNL animals.…”
Section: Resultsmentioning
confidence: 99%
“…Morphine, SR14150, and SR16835 produced antinociceptive effects, so in follow-up experiments, animals received a pretreatment of 1 mg/kg opioid antagonist naloxone or a pretreatment of 10 mg/kg NOP receptor antagonist SB-612111 (Zaratin et al, 2004) to determine whether drug-mediated effects were due to opioid or NOP receptor activity. The dose of naloxone chosen has been shown to reverse the effects of morphine, and the dose of SB-612111 was chosen on the basis of our previous experiments (Khroyan et al, 2007b;Toll et al, 2009). The antagonists were given 10 min before the injection of morphine, SR14150, or SR16835.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The behavioral results obtained with BU08028 can also be compared with other bifunctional /NOP receptor ligands that we have characterized previously. We have demonstrated previously that SR14150 and SR16435, both with high affinity and partial agonist activity at NOP and receptors, have antinociceptive activity that is inhibited by naloxone and potentiated by the NOP receptor antagonist SB612111 Toll et al, 2009). SR16435, which has an in vitro profile strikingly similar to BU08028, produces antinociception and CPP, indicating that, like BU08028, the NOP component is not sufficient to block the rewarding effect of the component.…”
Section: Discussionmentioning
confidence: 99%
“…However, the optimum profile of and NOP receptor affinity and/or efficacy for an optimum balance of analgesia to antagonism, reward to reward attenuation, and locomotor activation to sedation for a useful therapeutic profile cannot be predicted. We have demonstrated that such mixed NOP/ compounds can be developed with significant antinociceptive activity and greatly reduced reward, but to attenuate reward in a traditional NOP receptor nonopioid small-molecule pharmacophore (see Zaveri et al, 2005), the NOP component must overshadow the component with respect to affinity and/or efficacy (Khroyan et al, 2007;Toll et al, 2009). This is not the case with buprenorphine, in which the affinity is far greater than the NOP receptor affinity.…”
Section: Introductionmentioning
confidence: 99%